Evaluation of bond strength of silorane and methacrylate based restorative systems to dentin using different cavity models - Stephano Zerlottini Isaac; Ana Claudia Pietrobom Bergamin; Cecilia Pedroso Turssi; Flavia Lucisano Botelho do Amaral; Roberta Tarkany Basting; Fabiana Mantovani Gomes Franca (University of São Paulo, 2013)
OBJECTIVE: The aim of this in vitro study was to evaluate the microtensile bond strength (µTBS) to dentin of two different restorative systems: silorane-based (P90), and methacrylate-based (P60), using two cavity models. MATERIAL AND METHODS: Occlusal enamel of 40 human third molars was removed to expose flat dentin surface. Class I cavities with 4 mm mesial-distal width, 3 mm buccal-lingual width and 3 mm depth (C-factor=4.5) were prepared in 20 teeth, which were divided into two groups (n=10) restored with P60 and P90, bulk-filled after dentin treatment according to manufacturer's instructions. Flat buccal dentin surfaces were prepared in the 20 remaining teeth (C-factor=0.2) and restored with resin blocks measuring 4x3x3 mm using the two restorative systems (n=10). The teeth were sectioned into samples with area between 0.85 and 1.25 mm2 that were submitted to µTBS testing, using a universal testing machine (EMIC) at speed of 0.5 mm/min. Fractured specimens were analyzed under stereomicroscope and categorized according to fracture pattern. Data were analyzed using ANOVA and Tukey Kramer tests. RESULTS: For flat surfaces, P60 obtained higher bond strength values compared with P90. However, for Class I cavities, P60 showed significant reduction in bond strength (p<0.05). No statistical difference between restorative systems was shown for Class I cavity model (p>0.05), or between Class I Cavity and Flat Surface group, considering P90 restorative system (p>0.05). Regarding fracture pattern, there was no statistical difference among groups (p=0.0713) and 56.3% of the fractures were adhesive. CONCLUSION: It was concluded that methacrylate-based composite µTBS was influenced by cavity models, and the use of silorane-based composite led to similar bond strength values compared to the methacrylate-based composite in cavities with high C-factor.